Relationship Among Inflammation, Overweight Status, and Cognitive Impairment in a Community-Based Population of Chinese Adults - Wang, Jing; Wang, Anxin; Zhao, Xingquan (Frontiers in Neurology, 2020)
Purpose: To determine the association overweight and high-sensitivity C-reactive protein (hs-CRP) with the risk odds of cognitive impairment as well as its subtypes based on the Asymptomatic Polyvascular Abnormalities Community (APAC) study in China. Materials and Methods: We conducted a cross-sectional analysis of the follow-up data of 2012 from the APAC study. The Chinese version of the MMSE was used as a cognitive screener, and an MMSE score <24 is generally accepted as indicating cognitive impairment. In all, 5,440 participants were enrolled in the APAC study. We excluded 1,565 participants who had incomplete data of Mini-Mental State Examination (MMSE) score, leaving 2,203 men and 1,672 women in the final analyses. Multivariable logistic regression was used to estimate the interactions of hs-CRP levels with body mass index (BMI) on the effects of cognitive impairment and its subtypes. Results: Of the 3,875 participants aged 40-90 years (median age 51.64y) were enrolled in this study, only and 1,788 (46.1%) were overweight. Before and after adjusting for all possible confounders, such as age, sex, BMI, education, current smoking, drinking, physical activity, hypertension, hyperlipidemia, diabetes and hs-CRP, elevated hs-CRP levels increased the risk of were associated with cognitive impairment in normal-weight participants (crude OR: 2.08, 95%CI: 1.28–3.37, p=0.003; adjusted OR: 2.06, 95%CI: 1.03–4.10, p=0.04crude: OR 2.08, 95%CI: 1.28–3.37, p=0.003; adjusted OR: 1.97, 95%CI: 1.06–3.65, p=0.03), but not in overweight participants (crude OR: 0.88, 95%CI: 0.53–1.45, p=0.61; adjusted OR: 0.57, 95%CI: 0.29–1.11, p=0.10). There was no statistically significant evidence for the interaction between hs-CRP and BMI on any cognitive sub-item. Conclusion: Elevated hs-CRP levels increase the risk odds of cognitive impairment in normal-weight participants, but not in overweight participants.